Perspektif Pengembangan Ekonomi Kedelai di Indonesia (Forum Penelitian Agro Ekonomi, 2016)
EnglishSoybean as one of agricultural commodity plays an important role in the Indonesian' economy. The role intertwined in the food crops demand, consumption, trade, and the farmers' income. Technical as well as economical aspects are faced by the Indonesian government to promote local or domestic soybean, especially when it has to compete with the imported soybean. Presently, soybean farming system is financially profitable, taking the advantage of the Indonesian protection policy. Economically, soybean-farming system is inefficient due to inefficiency in using the domestic resources to meet the domestic demand and export promotion. This study concluded that several strategic policies that have to be taken by Indonesian' government to increase the competitiveness of local or domestic soybean are: (1) to promote suitable region specifically for soybean, (2) to increase soybean yield or productivity through introducing the high yield varieties adapted to the region, efficiency on the on-farm management, (3) import tax to protect domestic soybean, (4) to introduce the new post harvest technology (to minimize harvest losses) and other non-price policy. IndonesianKomoditas kedelai memegang peranan penting dalam ekonomi rumah tangga petani, konsumsi pangan, kebutuhan dan perdagangan pangan nasional. Pengembangan komoditas ini dihadapkan pada pemasalahan teknis, sosial-ekonomi, dan defisit perdagangan dan daya saing dengan kedelai impor. Usahatani kedelai menguntungkan secara finansial karena didukung oleh kebijaksanaan protektif. Komoditas kedelai secara ekonomi dinilai kurang efisien dalam pemanfaatan sumber daya domestik untuk memenuhi kebutuhan dalam negeri dan lebih-lebih lagi untuk tujuan promosi ekspor. Kebijaksanaan strategis yang perlu di lakukan untuk meningkatkan daya saing kedelai nasional adalah pemilihan wilayah pengembangan yang sesuai, peningkatan produktivitas melalui penciptaan varietas dengan adaptasi dan potensi hasil yang lebih tinggi serta perbaikan manajemen usahatani, kebijaksanaan tarif impor yang memadai untuk mendorong adopsi teknologi dan peningkatan produksi. Disamping peningkatan produktivitas dan efisiensi, perlu terus diupayakan peningkatan stabilitas hasil, penekanan senjang hasil, kehilangan hasil saat panen dan pengolahan, serta kebijaksanaan nonharga lainnya.